THE PHENOMENON OF MARRIAGE DELAY IN THE MODERN ERA FROM AN ISLAMIC LAW PERSPECTIVE (CASE STUDY OF MASTER'S STUDENTS IN FAMILY LAW AT THE STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA) - Nurheliza, Siti; Adly, Muhammad Amar (Hukum tata Negara/Siyasah, 2026)
This study aims to analyze the phenomenon of delayed marriage among Master of Family Law students at the State Islamic University of North Sumatra and review it from an Islamic law perspective. This study uses a qualitative method with a legal-normative and sociological approach, through literature study and in-depth interviews with students who have delayed marriage. The results of the study show that the main factors for postponing marriage include economic and financial pressures, the priority of completing education, and mental and emotional unpreparedness. From an Islamic law perspective, marriage is a highly recommended sunnah of the Prophet, but the law on postponing marriage is contextual and can change according to individual circumstances. Postponing marriage with a valid excuse, such as economic limitations, focus on studying, and efforts to prepare oneself, is considered permissible and justifiable based on the principle of maqasid al-syar'i, especially in maintaining safety of life, continuity of reason, preservation of offspring, and security of property. The implications of postponing marriage have two sides, namely positive impacts in the form of increased focus on education, career, and self-development, as well as negative impacts such as emotional pressure, loneliness, difficulty controlling sexual desire, and social pressure. This study concludes that postponing marriage among students can be understood as an effort to achieve long-term benefits as long as it is done proportionally, responsibly, and based on Islamic values.Keywords: Postponement of Marriage, Modern Era, Islamic Law